Inverse analyses of effective diffusion parameters relevant for a two-phase moisture model of cementitious materials. (April 2018) - Addassi, Mouadh; Johannesson, Björn; Wadsö, Lars
Abstract: Here we present an inverse analyses approach to determining the two-phase moisture transport properties relevant to concrete durability modeling. The purposed moisture transport model was based on a continuum approach with two truly separate equations for the liquid and gas phase being connected by the sorption kinetics. The moisture properties of ten binder-systems containing fly ash, calcined clay, burnt shale and gray micro-filler, were investigated experimentally. The experiments used were, (i) sorption test (moisture fixation), (ii) cup test in two different relative humidity intervals, (iii) drying test, and, (iv) capillary suction test. Mass change over time, as obtained from the drying test, the two different cup test intervals and the capillary suction test, was used to obtain the effective diffusion parameters using the proposed inverse analyses approach. The moisture properties obtained with the proposed inverse analyses method provide a good description of the test period for the ten different binder-systems.